Patterns of regional lung physiology in cystic fibrosis using ventilation magnetic resonance imaging and multiple-breath washout - Smith, Laurie J.; Collier, Guilhem J.; Marshall, Helen; Hughes, Paul J.C.; Biancardi, Alberto M.; Wildman, Martin; Aldag, Ina; West, Noreen; Horsley, Alex; Wild, Jim M. (The European respiratory journal, 2018)
Hyperpolarised helium-3 ( 3 He) ventilation magnetic resonance imaging (MRI) and multiple-breath washout (MBW) are sensitive methods for detecting lung disease in cystic fibrosis (CF). We aimed to explore their relationship across a broad range of CF disease severity and patient age, as well as assess the effect of inhaled lung volume on ventilation distribution. 32 children and adults with CF underwent MBW and 3 He-MRI at a lung volume of end-inspiratory tidal volume (EI V T ). In addition, 28 patients performed 3 He-MRI at total lung capacity. 3 He-MRI scans were quantitatively analysed for ventilation defect percentage (VDP), ventilation heterogeneity index (VHI) and the number and size of individual contiguous ventilation defects. From MBW, the lung clearance index, convection-dependent ventilation heterogeneity (Scond) and convection–diffusion-dependent ventilation heterogeneity (Sacin) were calculated. VDP and VHI at EI V T strongly correlated with lung clearance index (r=0.89 and r=0.88, respectively), Sacin (r=0.84 and r=0.82, respectively) and forced expiratory volume in 1 s (FEV 1 ) (r=−0.79 and r=−0.78, respectively). Two distinct 3 He-MRI patterns were highlighted: patients with abnormal FEV 1 had significantly (p<0.001) larger, but fewer, contiguous defects than those with normal FEV 1 , who tended to have numerous small volume defects. These two MRI patterns were delineated by a VDP of ∼10%. At total lung capacity, when compared to EI V T , VDP and VHI reduced in all subjects (p<0.001), demonstrating improved ventilation distribution and regions of volume-reversible and nonreversible ventilation abnormalities.